A Review on Concrete Strength Prediction Models Based on Machine Learning Algorithms (International Journal of Innovative Research in Engineering & Management, 2023)
In the present time, machine learning  algorithms are used for design concreate strength  prediction models due to numerous advantages over the  manual methods such as cost and time effective and more  effectively predict the strength based on the historical  information. Therefore, the main aim of this paper, is to  study and analyse the various machine learning algorithms  are used to design concrete strength prediction model. In  the literature, last five years paper is taken under  consideration. Based on literature survey, open research  gaps are defined which helps the other authors to  contribute their research in this area.
Keywords: Concrete Strength Prediction; Machine Learning Algorithms